2022
DOI: 10.3389/fneur.2022.880732
|View full text |Cite
|
Sign up to set email alerts
|

Microscopic Transsphenoidal Resection of Giant Pituitary Adenomas: Analysis of the Factors Limiting the Degree of Resection in 73 Cases

Abstract: PurposeTo analyze the risk factors affecting the gross-total resection of giant pituitary adenomas using a transsphenoidal approach under a microscope to provide a reference basis for formulating an appropriate surgical strategy.MethodsThe clinical data of patients who underwent microscopic transsphenoidal resection of giant pituitary adenomas in a single center from January 2011 to December 2020 were retrospectively analyzed. Based on magnetic resonance imaging and surgical records, the predictive factors aff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…24 Special care to remove the tumor and relieve the mass effect without compromising neurological function to the greatest degree is important to ensure the survival and quality of life of patients with pituitary tumors, and this has remained a challenge. 25,26 Our analysis studying the duration of surgery showed that gross total resection was a predictor of a shorter surgery, regardless of surgical approach. This finding could be due to the soft consistency of an adenoma, making gross total resection achievable.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…24 Special care to remove the tumor and relieve the mass effect without compromising neurological function to the greatest degree is important to ensure the survival and quality of life of patients with pituitary tumors, and this has remained a challenge. 25,26 Our analysis studying the duration of surgery showed that gross total resection was a predictor of a shorter surgery, regardless of surgical approach. This finding could be due to the soft consistency of an adenoma, making gross total resection achievable.…”
Section: Discussionmentioning
confidence: 89%
“…28 Other barriers to a gross total resection of pituitary tumors can be the anatomical location of the tumor, specifically if it has a greater suprasellar extension or cavernous sinus invasion. 25,26 A study by Pei et al studied factors limiting gross total resection in pituitary adenomas and found that with microscopic resection, cavernous sinus invasion and greater suprasellar expansion can serve as obstacles towards achieving gross total resection. 25 However, our analysis did not indicate a significant interaction between cavernous sinus invasion, suprasellar extension, and gross total resection.…”
Section: Discussionmentioning
confidence: 99%
“…This assumption is incorrect because a minority of PitNETs might require transcranial surgery 6 ; furthermore, it is known that ETSS might allow the resection of PitNETs that would not be treated safely with MTSS. 6-8…”
mentioning
confidence: 99%
“…This assumption is incorrect because a minority of PitNETs might require transcranial surgery 6 ; furthermore, it is known that ETSS might allow the resection of PitNETs that would not be treated safely with MTSS. [6][7][8] Tumor dimensions were graded only as microadenomas or macroadenomas, making it impossible to extrapolate the prevalence of giant adenomas in the studied cohort. Centers using only microsurgery might have treated larger PitNETs with transcranial rather than TS.…”
mentioning
confidence: 99%